Renovation and reconstruction of a neoclassical building on the example of a Public City Library in Nowa Sól = Renowacja i przebudowa obiektu neoklasycystycznego na przykładzie budynku Miejskiej Biblioteki Publicznej w Nowej Soli - Kucharczyk, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The building of the Nowa Sól public library is located on Bankowa Street, in the Lubuskie Voivodeship. The new seat of the library has been here since 2011; it had previously been located in the building on Parafialna and Szkolna Streets, which did not comply with the requirements of a comfortable library and reading room. Renovations and reconstructions of this neoclassical building began in 2007 and took four years to finish.
Keywords: Nowa Sól; Miejska Biblioteka Publiczna (Nowa Sól); renowacja; przebudowa; neoklasycyzm; public library; renovation; reconstruction; neoclassical architecture